2013
DOI: 10.1016/j.scitotenv.2012.12.058
|View full text |Cite
|
Sign up to set email alerts
|

The potential of a salt-tolerant plant (Distichlis spicata cv. NyPa Forage) to treat effluent from inland saline aquaculture and provide livestock feed on salt-affected farmland

Abstract: Dryland salinity is a major problem affecting food production from agricultural land in Australia and throughout the world. Although there is much interest in using saline groundwater to grow marine fish on salt-affected farmland, the disposal of nutrient enriched, saline aquaculture effluent is a major environmental problem. We investigated the potential of the salt-tolerant NyPa Forage plant (Distichlis spicata L. Greene var. yensen-4a) to trap nutrients from saline aquaculture effluent and subsequently to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 59 publications
(105 reference statements)
4
17
0
Order By: Relevance
“…However, despite the existing variability in terms of nutrient removal, which seems to depend on system design, flow regime, nutrient concentration and species (Buhmann & Papenbrock 2013b), not all setups per se are equally effective for nutrient removal, taking into account the specific objectives established for each CW. N removal capacity attained around 90% or more in 4 of the studies that were surveyed , Lin et al 2002b, Webb et al 2012, Lymbery et al 2013, and only 1 experiment reported a low N removal capacity (11%) (de Lange & Paulissen 2016). While in some of the studies P removal was close to 100% (e.g.…”
Section: Halophytes In Aquaculture: Facts and Figuresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite the existing variability in terms of nutrient removal, which seems to depend on system design, flow regime, nutrient concentration and species (Buhmann & Papenbrock 2013b), not all setups per se are equally effective for nutrient removal, taking into account the specific objectives established for each CW. N removal capacity attained around 90% or more in 4 of the studies that were surveyed , Lin et al 2002b, Webb et al 2012, Lymbery et al 2013, and only 1 experiment reported a low N removal capacity (11%) (de Lange & Paulissen 2016). While in some of the studies P removal was close to 100% (e.g.…”
Section: Halophytes In Aquaculture: Facts and Figuresmentioning
confidence: 99%
“…The ex peri ments were performed in diverse geographic regions and climates ( Fig. 4): the arid climates of southern Israel (Shpigel et al 2013) and southwestern USA , the humid subtropical regions of Taiwan (Lin et al 2002b(Lin et al , 2003(Lin et al , 2005 and south eastern USA (Boxman et al 2017), the oceanic climate of northwestern Europe (Webb et al 2012, 2013, Quintã et al 2015a, de Lange & Paulissen 2016) and the Mediterranean climate of southwestern Australia (Lymbery et al 2006(Lymbery et al , 2013. Yet, the diversity of studies is still low and additional studies with endemic species in different climate regions are needed.…”
Section: Halophytes In Aquaculture: Facts and Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…During these phases, approximately 5 m 2 of floating beds was maintained in the bivalve tank, and the S. salicornia grew rapidly. The saltmarsh root system could capture large suspended particles, such as detritus, which could then precipitate (Li, Song, Li, Lu & Nishimura ; Lymbery, Kay, Doupe, Partridge & Norman ). Moreover, the bivalves could assimilate the remaining small debris and microalgae via their filter – feeding effect (Jones, Preston & Dennison ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Shpigel et al (2013), the authors demonstrated that nitrogen, phosphorous, and total suspended solids were efficiently removed using Salicorna as a biofilter within a constructed wetland. In another study by Lymbery et al (2013), wetlands removed 60-90% of total nitrogen loads and at least 85% of total phosphorus, and orthophosphate loads from the aquaculture effluent.…”
Section: Wetlandsmentioning
confidence: 98%